2016
DOI: 10.1155/2016/6189374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Na+Current and Mechanogated Channels in Myofibroblasts on Myocyte Excitability and Repolarization

Abstract: Fibrotic remodeling, characterized by fibroblast phenotype switching, is often associated with atrial fibrillation and heart failure. This study aimed to investigate the effects on electrotonic myofibroblast-myocyte (Mfb-M) coupling on cardiac myocytes excitability and repolarization of the voltage-gated sodium channels (VGSCs) and single mechanogated channels (MGCs) in human atrial Mfbs. Mathematical modeling was developed from a combination of (1) models of the human atrial myocyte (including the stretch act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Human cardiac fibroblasts (Chatelier et al, 2012;Koivumaki et al, 2014;Li et al, 2009;Zhan et al, 2016) Voltage-gated K + channels Transient outward K + current, I to Delayed rectified K + currents: I K , I Kf Human and rat cardiac fibroblast Rook et al, 1992; Neonatal rat cardiac fibroblasts (Rook et al, 1992;Walsh & Zhang, 2008) Inward-rectifier K + channels K ir , IK v Human lung fibroblasts (Roach et al, 2013) Human cardiac fibroblasts (Aguilar et al, 2014;Li et al, 2009) Canine atrial fibroblasts (Benamer et al, 2009) ATP-activated K + channels K ATP Rat ventricular fibroblasts (Benamer et al, 2009) Human dermal fibroblasts (Bednarczyk et al, 2018) TRP channels TRPA1, TRPC1, TRPC3, TRPC4, TRPC6, TRPV4, TRPM2, TRPM7 Human and mouse lung fibroblasts (Hofmann et al, 2017;Rahaman et al, 2014;Wei et al, 2009;Yonezawa et al, 2016) Mouse proximal tubular cells (Mannaa et al, 2018) Human and rat hepatic stellate cells (Song et al, 2014) Human, rat, and mouse kidney fibroblasts (Saliba et al, 2015) Rat ventricular fibroblasts (Rose et al, 2007) Human, rat, and mouse cardiac fibroblasts (Chen et al, 2010;Du et al, 2010;Li et al, 2019;Mannaa et al, 2018;Oguri et al, 2014;Rahaman et al, 2014;Runnels et al, 2002;Saliba et al, 2015;Song et al, 2014) Cl − channels I Cl-swell , ClC-3, I Cl Human cardiac fibroblasts (Li et al, 2009;…”
Section: Types Of Ion Channels Names Of Ion Channels Cell Types Exprementioning
confidence: 99%
“…Human cardiac fibroblasts (Chatelier et al, 2012;Koivumaki et al, 2014;Li et al, 2009;Zhan et al, 2016) Voltage-gated K + channels Transient outward K + current, I to Delayed rectified K + currents: I K , I Kf Human and rat cardiac fibroblast Rook et al, 1992; Neonatal rat cardiac fibroblasts (Rook et al, 1992;Walsh & Zhang, 2008) Inward-rectifier K + channels K ir , IK v Human lung fibroblasts (Roach et al, 2013) Human cardiac fibroblasts (Aguilar et al, 2014;Li et al, 2009) Canine atrial fibroblasts (Benamer et al, 2009) ATP-activated K + channels K ATP Rat ventricular fibroblasts (Benamer et al, 2009) Human dermal fibroblasts (Bednarczyk et al, 2018) TRP channels TRPA1, TRPC1, TRPC3, TRPC4, TRPC6, TRPV4, TRPM2, TRPM7 Human and mouse lung fibroblasts (Hofmann et al, 2017;Rahaman et al, 2014;Wei et al, 2009;Yonezawa et al, 2016) Mouse proximal tubular cells (Mannaa et al, 2018) Human and rat hepatic stellate cells (Song et al, 2014) Human, rat, and mouse kidney fibroblasts (Saliba et al, 2015) Rat ventricular fibroblasts (Rose et al, 2007) Human, rat, and mouse cardiac fibroblasts (Chen et al, 2010;Du et al, 2010;Li et al, 2019;Mannaa et al, 2018;Oguri et al, 2014;Rahaman et al, 2014;Runnels et al, 2002;Saliba et al, 2015;Song et al, 2014) Cl − channels I Cl-swell , ClC-3, I Cl Human cardiac fibroblasts (Li et al, 2009;…”
Section: Types Of Ion Channels Names Of Ion Channels Cell Types Exprementioning
confidence: 99%
“…In addition, I Na_Mfb is added in the Mfb model. According to our previous work [9], equations of I Na_Mfb is given by…”
Section: Model Of Human Atrial Mfbsmentioning
confidence: 99%
“…In previous study, we have found that the Nav 1.5  subunit, which generates I Na_myofb , regenerated action potentials (APs) in myocytes and Mfbs [9]. In this study, we aimed to investigate the role of Mfbs on the mechanical contraction of cardiac fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has found that I Na_myofb and I MGC_Mfb regenerated APs in myocytes and Mfbs [28]. In this study, we aimed to investigate the role of I SAC , I Na_Mfb , and I MGC_Mfb in the mechanical contraction of cardiac myocyte.…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, processes of fibrotic remodeling are represented as fibroblast proliferation and phenotype switching [23, 24]. Simulation results showed that coupling of fibroblasts or Mfbs to atrial myocytes resulted in shorter duration of the action potential (APD), slower conduction, and spiral wave breakups [2528].…”
Section: Introductionmentioning
confidence: 99%